Understanding Organismal Capacity to Respond to Anthropogenic Change: Barriers and Solutions. (19th July 2021) - Gabor, Caitlin R; Kivlin, Stephanie N; Hua, Jessica; Bickford, Nate; Reiskind, Martha O Burford; Wright, Timothy F
Synopsis: Global environmental changes induced by human activities are forcing organisms to respond at an unprecedented pace. At present we have only a limited understanding of why some species possess the capacity to respond to these changes while others do not. We introduce the concept of multidimensional phenospace as an organizing construct to understanding organismal evolutionary responses to environmental change. We then describe five barriers that currently challenge our ability to understand these responses: (1) Understanding the parameters of environmental change and their fitness effects, (2) Mapping and integrating phenotypic and genotypic variation, (3) Understanding whether changes in phenospace are heritable, (4) Predicting consistency of genotype to phenotype patterns across space and time, and (5) Determining which traits should be prioritized to understand organismal response to environmental change. For each we suggest one or more solutions that would help us surmount the barrier and improve our ability to predict, and eventually manipulate, organismal capacity to respond to anthropogenic change. Additionally, we provide examples of target species that could be useful to examine interactions between phenotypic plasticity and adaptive evolution in changing phenospace.